Experimental Investigation of Water-Inrush Risk Based on Permeability Evolution in Coal Mine and Backfill Prevention Discussion - Meng Li; Jixiong Zhang; Weiqing Zhang; Ailing Li; Wei Yin (Geofluids)
Induced by coal mining, the fractures constantly occur in geologic strata until failure occurs, which provide channels for water flow. Therefore, it is essential to investigate the permeability evolution of rocks under load. Borehole sampling was conducted in a bedrock layer beneath an aquifer, and the permeability evolution of sandstone specimens under different confining pressures was tested in rock mechanics testing laboratories. The results indicated that the permeability gradually decreases with the increasing confining pressures, while the peak strength increases with the increase of confining pressures. The minimum and maximum permeabilities occurred in the sandstone specimens that were subjected to elastic deformation and strain-softening stages, respectively. The failure, and maximum permeability, of these sandstone specimens did not occur simultaneously. To prevent the flow channel being formed due to the development and failure of rock fractures, a method of backfill gob was proposed and also the influence of backfill on fracture development was discussed.